Velocity Measurements Using High-Speed Imaging System for Impact Test - Anwar, P. P. Abdul Majeed; Abdul Aziz, Jaafar; Sapuan, S. M.; Shahnor, Basri (Trans Tech Publications, Switzerland, 2014)
This paper presents the velocity measurements for an impact test on a laminated fibre-glass composite plate. The free flight kinematic properties of a blunt-nosed cylindrical projectile on the upstream and downstream of a test coupon were measured using a high-speed camera imaging system. A visual geometric detection technique is discussed and it is shown that the uncertainties of velocity measurements are associated with an imposed constraint on the camera viewing area and shutter speed.